Winning or not winning: the influence on coach-athlete relationships and goal achievement - Trocado Mata, R.; da Silva Gomes, A. R. (Journal of Human Sport & Exercise, 2013)
This study analyzes the relation between sports success and athletes` perception of coaches` leadership, athletes` satisfaction with coaches` leadership, coach-athlete compatibility, and goal achievement. Sixty-six athletes who qualified for the final Division I play-offs of a professional volleyball championship were grouped into winning (n = 21) and non-winning teams (n = 45). Leadership styles, satisfaction with leadership, coach-athlete compatibility, and goal achievement were evaluated. Analysis of variance with repeated-measures revealed that the winning teams evaluated their coaches` vision, inspiration, technical coaching, positive feedback, and active management more positively than non-winning teams and that their satisfaction with coaches` strategies increased over time. A multivariate analysis of variance (MANOVA) indicated that the winning teams` perceived achievement of personal and team goals was greater than that of the non-winning teams. Sports success was associated with athletes` positive evaluation of coaches` leadership, satisfaction with coaches` strategy, and higher perceived goal attainment.